Can Court Diversion Improve School Attendance among Elementary Students? Evidence from Five School Districts. Issue 4 (1st October 2020) - Lee, Won Fy; McNeely, Clea A.; Rosenbaum, Janet E.; Alemu, Besufekad; Renner, Lynette M.
Abstract: We examined the effect on attendance of a truancy court-diversion program for elementary students. Truancy court-diversion programs represent a shift from a law-and-order approach toward a public health model to address school absenteeism. Instead of directly referring parents of truant elementary students to child protection services or juvenile court, most court-diversion programs educate parents about the importance of school attendance and create an attendance contract that includes social service referrals. Despite being widely implemented, truancy court-diversion models have not been rigorously evaluated. Using 10 years of administrative data from multiple state and local agencies from Minnesota, we constructed a counterfactual of students from schools that did not implement truancy court-diversion. We used difference-in-differences methods to test whether parent education and attendance contracts improved attendance relative to direct referral to child protection services or court. We failed to reject the null hypothesis of no program effect. Most truancy program evaluations use a pre- and post-mean comparison, but our analysis suggested that the magnitude of the bias in such studies is substantial because absenteeism showed a pattern of regression to the mean.